2013
DOI: 10.1530/eje-13-0142
|View full text |Cite
|
Sign up to set email alerts
|

Surgery for adrenocortical carcinoma in The Netherlands: analysis of the national cancer registry data

Abstract: Objective: Adrenocortical carcinoma (ACC) is a rare disease with an estimated incidence of one to two cases per 1 million inhabitants. The Dutch Adrenal Network (DAN) was initiated with the aim to improve patient care and to stimulate scientific research on ACC. Currently, not all patients with ACC are treated in specialized DAN hospitals. The objective of the current investigation was to determine whether there are differences in survival between patients operated on in DAN hospitals and those operated on in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
28
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(32 citation statements)
references
References 28 publications
3
28
0
Order By: Relevance
“…Resection status is one of the most important prognostic factors. To reduce the amount of recurrences, it is recommended to perform adrenalectomies only in specialized centers performing at least 20 adrenalectomies per year (Kerkhofs et al 2013a, Ronchi et al 2014a. A recent systematic review reported that open adrenalectomy with lymph node dissection should be regarded as standard treatment for ACC (Bellantone et al 2015).…”
Section: Current Therapeutic Strategiesmentioning
confidence: 99%
“…Resection status is one of the most important prognostic factors. To reduce the amount of recurrences, it is recommended to perform adrenalectomies only in specialized centers performing at least 20 adrenalectomies per year (Kerkhofs et al 2013a, Ronchi et al 2014a. A recent systematic review reported that open adrenalectomy with lymph node dissection should be regarded as standard treatment for ACC (Bellantone et al 2015).…”
Section: Current Therapeutic Strategiesmentioning
confidence: 99%
“…Regarding ACC, increasing evidence suggests that establishment of (inter)national collaborative networks of expert centres has a favourable effect on survival , Lombardi et al 2012, Kerkhofs et al 2013b. The concept that rare diseases should be treated in a limited number of specialized hospitals seems intuitively logical.…”
Section: Organization and Quality Of Carementioning
confidence: 99%
“…In selected patients presenting with metastasized disease, debulking surgery might yield a survival benefit (Kerkhofs et al 2013b, Dy et al 2015. Prospective studies on this topic are not yet available, and retrospective studies inevitably hold selection bias: chances are that patients who underwent debulking surgery were in better clinical condition compared to patients who were not operated on.…”
Section: Surgery: the Primary Treatment Modalitymentioning
confidence: 99%
“…2–4 Unfortunately, ACC is a highly malignant tumor, with up to 70% to 85% of patients experiencing recurrence after surgical resection. 3,57 In turn, 5-year overall survival (OS) estimates for patients with ACC range from 15% to 84% depending on the stage of disease at presentation. 5,79 The results of studies 10,11 have suggested that adjuvant mitotane therapy may improve the prognosis, although prospective data have been scarce because of the low incidence of ACC.…”
mentioning
confidence: 99%
“…3,57 In turn, 5-year overall survival (OS) estimates for patients with ACC range from 15% to 84% depending on the stage of disease at presentation. 5,79 The results of studies 10,11 have suggested that adjuvant mitotane therapy may improve the prognosis, although prospective data have been scarce because of the low incidence of ACC. While several clinicopathological factors have been associated with survival and the risk of recurrence, accurate prognostication among patients with ACC remains a challenge.…”
mentioning
confidence: 99%